Classification of nonlocal boundary-value problems on a narrow strip - Borok, V. M.; Kengne, E. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For a general linear partial differential equation with constant coefficients, we establish a well-posedness criterion for a boundary-value problem on a strip Π_y = ℝ × [0,Y] with an integral in a boundary condition. A complete classification of such problems based on their asymptotic properties as Y → 0 is obtained.